Report on business attachment with McDonald's. - Loh, Chor Hong. (2009)
This report forms the term paper and final business attachment report. It is written to apply our classroom knowledge and practical experience during our ten-week long programme. The topic chosen is on McDonald's marketing programme and the teenage market.